Thermo-economic Optimization of Solar Assisted Heating and Cooling (SAHC) System - A. Ghafoor; A. Munir (International Journal of Renewable Energy Development, 2014)
The energy demand for cooling is continuously increasing due to growing thermal loads, changing architectural modes of building, and especially due to occupants indoor comfort requirements resulting higher electricity demand notably during peak load hours. This increasing electricity demand is resulting higher primary energy consumption and emission of green house gases (GHG) due to electricity generation from fossil fuels. An exciting alternative to reduce the peak electricity consumption is the possible utilization of solar heat to run thermally driven cooling machines instead of vapor compression machines utilizing high amount of electricity. In order to widen the use of solar collectors, they should also be used to contribute for sanitary hot water production and space heating. Pakistan lying on solar belt has a huge potential to utilize solar thermal heat for heating and cooling requirement because cooling is dominant throughout the year and the enormous amount of radiation availability provides an opportunity to use it for solar thermal driven cooling systems. The sensitivity analysis of solar assisted heating and cooling system has been carried out under climatic conditions of Faisalabad (Pakistan) and its economic feasibility has been calculated using maximization of NPV. Both storage size and collector area has been optimized using different economic boundary conditions. Results show that optimum area of collector lies between 0.26m2 to 0.36m2 of collector area per m2 of conditioned area for ieff values of 4.5% to 0.5%. The optimum area of collector increases by decreasing effective interest rate resulting higher solar fraction. The NPV was found to be negative for all ieff values which shows that some incentives/subsidies are needed to be provided to make the system cost beneficial. Results also show that solar fraction space heating varies between 87 and 100% during heating season and solar fraction cooling between 55 and 100% during cooling season which indicates a huge amount of conventional energy saving potential.